E-Marketplace Penjualan Buah dan Minuman Pohon Lontar di Kabupaten Rembang - Yoga Prasetya; Tri Listiyorini; Endang Supriyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
Along with today's technological advances, it is not wrong to build a system that will make it easier for people to promote and sell a product that is unique to their area. Apart from having an impact on the economic sector, this will also have an impact on the social sector. For the economic sector, it is clear, that is, seen from the results of the community in selling their products. Then, for the social sector itself, the area or village of the community will be more widely known. . This research was made to fulfill a goal, namely to design and build a system for selling fruit and drinks from lontar trees located in Bogorame Village, Sulang District, Rembang Regency using the CodeIgniter Framework. The main purpose of this development system is to help residents in Bogorgame Village increase the number of sales of fruit and drinks from lontar trees. In this case, I made observations first to determine the formulation of the problem. Then to design and build the system I use the Waterfall method, the design of this system is website-based with the PHP programming language. At the information system design stage using UML (Unified Modeling Language), Database design and Interface design.